2011
DOI: 10.4081/or.2011.e13
|View full text |Cite
|
Sign up to set email alerts
|

Hip arthrodesis in the pediatric population: where do we stand?

Abstract: Reconstructive and salvage procedures have continued to evolve in orthopedic surgery with changing functional demands of the population as well as advances in implants and surgical techniques. What used to be popular or traditional care at some point may eventually become a thing of the past, and this is true as far as many orthopedic surgical procedures are concerned. Understanding the etiology, pathogenesis, and managing and postponing the destructive pathway of osteoarthritis (OA) has been the goal of ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 79 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…However, this technique is no longer ‘fashionable’ in Western Europe but should be considered as a valuable solution. 22 …”
Section: Biological Reconstructionmentioning
confidence: 99%
“…However, this technique is no longer ‘fashionable’ in Western Europe but should be considered as a valuable solution. 22 …”
Section: Biological Reconstructionmentioning
confidence: 99%
“…Secondly, because optimal bone contact was prioritised at the fusion site, the limb could be placed in the ideal functional position through the osteotomy site (15-40° flexion, 0-10° abduction and 0-10° external rotation). 1,[6][7]24,28 During the immediate postoperative period, patients were placed in skeletal traction for a period of two weeks. This facilitated soft tissue healing and wound review, while maintaining the optimal alignment, and allowed for some initial soft callus formation.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Management of paediatric and adolescent patients with end-stage hip arthritis remains challenging, and the trends in management have changed over time. 1,2 When hip preservation is not possible, the treatment options are either total hip replacement (THR) or hip arthrodesis. There is limited evidence to support the choice of one procedure over the other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown problems such as prosthetic loosening, wear, osteolysis, and shortening of prosthetic life span occur at a higher frequency in the pediatric population (Shrader, 2012). Compared to adults, pediatric THA is performed for higher levels of severity in conditions such as Legg‐Calve‐Perthes disease, slipped capital femoral epiphysis, developmental dysplasia of the hip, and avascular necrosis (Bittersohl et al, 2011; Sedrakyan et al, 2014), requiring more complex surgery. Furthermore, increased activity level in youths make surgeons wary of increased chance of revision (Halvorsen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%